2017
DOI: 10.1186/s12986-016-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Do metabolic syndrome and its components have an impact on bone mineral density in adolescents?

Abstract: In recent years, there has been growing concern about the occurrence of metabolic syndrome (MetS) at an early age and its effects on bone mass in adolescents. Adolescence is considered a critical period for bone mass gain. Impaired bone acquisition during this phase can lead to “suboptimal” peak bone mass and increase the risk of osteopenia/osteoporosis and fractures in old age. The objective of this review was to perform a critical analysis of articles that specifically focus on this age group, evaluating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…However, BMD values were lower ( p = 0.046) in boys with two aggregate factors (physical inactivity and sedentary lifestyle). This is worrisome because adolescence is considered a critical period for the gain of bone mass and an impaired bone acquisition during this phase may increase the risk of osteopenia/osteoporosis and fractures in old age [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BMD values were lower ( p = 0.046) in boys with two aggregate factors (physical inactivity and sedentary lifestyle). This is worrisome because adolescence is considered a critical period for the gain of bone mass and an impaired bone acquisition during this phase may increase the risk of osteopenia/osteoporosis and fractures in old age [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors describe a study that detected a negative correlation between hypercholesterolemia with BMD (lumbar spine) and BMC (Bone Mineral Content) and increased total cholesterol in overweight/obese girls, but not in boys. The authors further suggested that the risk of cardiovascular disease and osteoporosis later in life would be greater in these girls [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 18 ) Understanding how obesity and its metabolic consequences effect bone development in children, especially during the two years surrounding the adolescent growth spurt when peak bone mineral density occurs, is an important clinical question as impaired bone growth during this time likely leads to suboptimal peak bone mass, increasing the risk for fractures and developing osteoporosis later in life. ( 13 , 19 ) The aim of this study was to examine whether the relationship between whole body adiposity and DXA-derived total body bone mass in 9-to-12 year old girls differed depending on the number of CMRs present.…”
Section: Introductionmentioning
confidence: 99%
“…Also, these markers are thought to appear to correlate with clinical activity score and severity of urticaria [56][57][58]. Metabolic syndrome (MetS) involves dyslipidemia, central obesity, glucose intolerance, and high blood pressure [59]. Furthermore it has been reported that patients suffering from MetS had higher serum levels of inflammatory markers such as IL-1, IL-6, TNF, and CRP than healthy controls [60].…”
Section: Comorbidities and Possible Triggering Factorsmentioning
confidence: 99%
“…Thus, systemic inflammation promoted by MetS may play a role in CSU pathogenesis as well. Furthermore, some studies revealed that the levels of TNF and C3 were found significantly higher and correlated with more severe, uncontrolled urticaria symptoms in patients with CSU and MetS at the same time [59,60].…”
Section: Comorbidities and Possible Triggering Factorsmentioning
confidence: 99%